2016
DOI: 10.4172/2327-5073.1000259
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bacterial Vaginosis in Early Pregnancy and its Effect on Spontaneous Preterm Delivery and Preterm Premature Rupture of Membranes

Abstract: This is the published version of a paper published in Clinical Microbiology. Citation for the original published paper (version of record):Larsson, P-G., Poutakidis, G., Adolfsson, A., Charonis, G., Pasi, B. et al. (2016) Treatment of bacterial vaginosis in early pregnancy and its effect on spontaneous preterm delivery and preterm rupture of membranes. AbstractBackground: This study was conducted to investigate whether screening and treatment of bacterial vaginosis (BV) in early pregnancy reduces the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The prevalence of 16.6% recorded in this study lies within the documented reported prevalence of 6%-32% from studies conducted in different regions of the world [17]. This prevalence is also consistent with figures reported from south-east and north-east Nigeria by Adinma et al [11] and Ibrahim et al [12] but higher than finding of Larrson et al [18] and lower than findings of Afolabi et al [19] and Isik et al [20]. Higher prevalence rates of bacterial vaginosis than in the present study were also reported from other sub-Saharan countries such as Kenya, Botswana, and Zimbabwe [21].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of 16.6% recorded in this study lies within the documented reported prevalence of 6%-32% from studies conducted in different regions of the world [17]. This prevalence is also consistent with figures reported from south-east and north-east Nigeria by Adinma et al [11] and Ibrahim et al [12] but higher than finding of Larrson et al [18] and lower than findings of Afolabi et al [19] and Isik et al [20]. Higher prevalence rates of bacterial vaginosis than in the present study were also reported from other sub-Saharan countries such as Kenya, Botswana, and Zimbabwe [21].…”
Section: Discussionsupporting
confidence: 92%
“…For intravaginal antibiotic preparations, consistent declines in the prevalence of use were apparent from 2015; but such trends have not been reported elsewhere; and as for systemic antibiotics, prevalence rates were lower than reported in Denmark overall (8.9%) and throughout the 13 years. 9 , 23 While intravaginal clindamycin and metronidazole are the first and second line treatments for bacterial vaginosis, which occurs in about 10% of the Swedish pregnant population, 21 , 38 the absence of routine screening may lead to untreated subclinical cases and the disparity with our prevalence rates. Intestinal antibiotic preparations were seldom used, as those currently available on the Swedish market are used to treat Clostridioides difficile infections, whose incidence is extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes because of the similarity of the symptoms of bacterial vaginosis are confused with those of candida and treated accordingly. To differentiate between the two it is necessary to examine the discharge culture with a microscopic examination [32].…”
Section: Discussionmentioning
confidence: 99%